2022
DOI: 10.1080/10872981.2022.2133986
|View full text |Cite
|
Sign up to set email alerts
|

How are Medical Institutions Supporting the Well-being of Undergraduate Students? A Scoping Review

Abstract: Introduction Medical students experience significant stress and impacts on mood due to multiple factors. Unmitigated stress impacts both physical and mental health while increasing the risk of unethical behavior. It is important for medical institutions to identify strategies that effectively reduce perceived stress and improve the well-being of their students. Methods The authors undertook a scoping review of the literature to identify strategies implemented by medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
(54 reference statements)
0
0
0
1
Order By: Relevance
“…Por otro lado, el único estudio observacional incluído en la revisión "How are Medical Institutions Supporting the Well-being of Undergraduate Students? A Scoping Review" (14) no mostró beneficios; al contrario, se evidenció una disminución de la calidad de vida y sensación de bienestar un año después de las intervenciones. Las intervenciones electivas no centradas en mindfulness, que incluían terapia equina y promoción de actividad física, mostraron una reducción de los niveles de depresión, de la severidad y frecuencia del estrés, con un aumento de la sensación de diversión, mejoría en la relación con pares, así como crecimiento personal y desarrollo de herramientas de resiliencia.…”
Section: Revisiones Narrativas De La Literaturaunclassified
“…Por otro lado, el único estudio observacional incluído en la revisión "How are Medical Institutions Supporting the Well-being of Undergraduate Students? A Scoping Review" (14) no mostró beneficios; al contrario, se evidenció una disminución de la calidad de vida y sensación de bienestar un año después de las intervenciones. Las intervenciones electivas no centradas en mindfulness, que incluían terapia equina y promoción de actividad física, mostraron una reducción de los niveles de depresión, de la severidad y frecuencia del estrés, con un aumento de la sensación de diversión, mejoría en la relación con pares, así como crecimiento personal y desarrollo de herramientas de resiliencia.…”
Section: Revisiones Narrativas De La Literaturaunclassified
“…The strengths of this study include the use of validated and quantifiable outcome measures, as well as the longer-term follow-up (this was rare in the studies identified in the previously mentioned scoping review 11 ). It was important to attempt to quantify lifestyle behaviours and correlate them to outcomes in order to explore them as potential mediators or confounders, particularly since these were relevant to the content of the program.…”
Section: Original Research | Pilot Study Of An Extra-curricular Resil...mentioning
confidence: 99%